Role of Hydrogen Sulfide in Retinal Diseases - Du, Jiantong; Jin, Hongfang; Yang, Liu (Frontiers in Pharmacology, 2017)
As the third gasotransmitter, hydrogen sulfide (H2S) plays a crucial role in the physiology and pathophysiology of many systems in the body, such as the nervous, cardiovascular, respiratory, and gastrointestinal systems. The mechanisms for its effects, including inhibiting ischemic injury, reducing oxidative stress damage, regulating apoptosis, and reducing the inflammation reaction in different systems, have not been fully understood. Recently, H2S and its endogenous synthesis pathway were found in the mammalian retina. This review describes the production and the metabolism of H2S and the evidence of a role of H2S in the retina physiology and in the different retinal diseases, including retinal degenerative diseases and vascular diseases. In the retina, H2S is generated in the presence of cystathionine-β-synthase, cystathionine-γ-lyase, and 3-mercaptopyruvate sulfurtransferase from L-cysteine. The role of endogenous H2S and its physiologic effect in the retina are still elusive. However, strong evidence shows that retina-derived H2S might play protective or deleterious role in the pathogenesis of retinal diseases. For example, by regulating Ca2+ influx, H2S can protect retinal neurons against light-induced degeneration. H2S preconditioning can mediate the anti-apoptotic effect of retinal ganglion cells in retinal ischemia/reperfusion injury. Treatment with H2S in rats relieves diabetic retinopathy by suppressing oxidative stress and reducing inflammation. Further studies would greatly improve our understanding of the pathophysiologic mechanisms responsible for retinal diseases and the potential for the H2S-related therapy of the retinal diseases as well.